Pentingnya Gen dalam Membentuk Kepribadian Anak - Zuyyina Candra Kirana (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2019)
Man was born according to his fitrah. The phylogenetic theory contains the innate, both genetically and other innate, but this is not an absolute being, but also in the developmental process that influences it. Islam also looks at genetic and environmental factors in relation to personality formation. Human beings and all the growth and characteristics are the embodiment of two factors, namely genetic factors (hereditary) and the environment. This paper is intended to enlighten that in the perspective of Islamic genetics and environment both play an important role for personality development. Because one's personal development is a result of the interaction of genetics and environment.